IDENTIFICATION OF INCOMPLETE FILLMENT OF MEDICAL RECORDS DOCUMENTS BASED ON EXPECTANCE MOTIVATION THEORY IN RSUD dr. R. KOESMA TUBAN - Adibah Enggar; Surotul Ilmiah; Esty Yunitasari (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Completeness of medical record documents becomes important because it describes the practice of quality services. RSUD dr. R. Koesma Tuban have problems with completeness of medical record documentation. Incompleteness medical record documentation of outpatient at RSUD dr. R. Koesma Tuban was rated at 87, 67%. The object of this study was to identify the incompleteness of medical record documentation of outpatient based on Victor Vroom expectancy theory motivation at RSUD dr. R. Koesma Tuban. The present study conducts a cross-sectional, descriptive research during May 2021 through to use questionnaires and observation on medical record documentation of outpatient. The respondents of this study were personnel who were filling the outpatient medical record documentation. These people were 5 doctors, 5 refractions, and 6 nurses. The result of the study showed that Filling of the medical record documentation at RSUD dr. R. Koesma Tuban was low. Motivation has driving factor to the incompleteness of outpatient medical record documentation at RSUD dr. R. Koesma Tuban. Suggestions given to monitoring the performance to complete the medical record documentation of outpatient. Keywords : hospital, incompleteness, medical record, motivation, outpatient, victor vroom